A novel prognostic nomogram utilizing the 2018 FIGO staging system for cervical cancer: A large multicenter study. Issue 1 (3rd May 2021) - Tang, Xiaoyan; Guo, Chenyan; Liu, Songping; Guo, Jingjing; Hua, Keqin; Qiu, Junjun
Abstract: Objective: To evaluate the prognostic performance of the revised 2018 FIGO staging system for cervical cancer. Methods: This retrospective multicenter study enrolled cervical cancer patients with 2009 FIGO Stage IA1–IIA2 who underwent surgeries between January 2006 and December 2017 in four tertiary hospitals. Patients were restaged according to the 2018 FIGO staging system by reviewing their medical data. Results: Of 3238 cervical cancer patients included, 1841 (56.9%) patients were restaged: 641 (34.9%) due to tumor size, 544 (29.5%) due to lymph node metastasis, 614 (33.4%) due to the inconsistency between pre‐ and postoperative assessments, and 42 due to the cancellation of invasion width in Stage IA. After restaging, a clear tendency of decreased recurrence‐free survival (RFS) and overall survival (OS) with increasing stage was observed. Multivariate Cox analysis showed that 2018 FIGO stage, parametrial involvement, and histology were independent prognostic factors for both OS and RFS ( P  < 0.05). Based on these factors, we established predictive nomograms with c‐indexes of 0.735 and 0.721, showing good predictive ability for cervical cancer. Conclusion: The revised 2018 FIGO staging system can better reflect the survival of cervical cancer patients. Based on it, we established a nomogram that can predict the prognosis of cervical cancer patients more precisely. Synopsis: The 2018 FIGO staging system for cervical cancer can better reflect the survival of patients; based on it, a prognostic nomogram was established.